2009
DOI: 10.1016/j.physleta.2009.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Cryptanalysis of a chaos-based image encryption algorithm

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited.In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(48 citation statements)
references
References 2 publications
0
48
0
Order By: Relevance
“…1) The secret keys of original algorithm are parameters p, q, n of Arnold cat map and initial values x 0 , y 0 , z 0 of Chen's chaotic system, the encryption steps are as follows: 2) The image firstly be shuffled by Arnold cat map as (2), then the shuffled image is converted into a sequence S; 3) A pseudo random key sequence K is produced by Chen's chaotic system (4) subsequently. Using K to do bitwise XOR operation with S, the encrypted sequence C can be produced as:…”
Section: Original Image Cryptosystemmentioning
confidence: 99%
See 2 more Smart Citations
“…1) The secret keys of original algorithm are parameters p, q, n of Arnold cat map and initial values x 0 , y 0 , z 0 of Chen's chaotic system, the encryption steps are as follows: 2) The image firstly be shuffled by Arnold cat map as (2), then the shuffled image is converted into a sequence S; 3) A pseudo random key sequence K is produced by Chen's chaotic system (4) subsequently. Using K to do bitwise XOR operation with S, the encrypted sequence C can be produced as:…”
Section: Original Image Cryptosystemmentioning
confidence: 99%
“…The scheme can't resist chosen-plaintext attack and known-plaintext attack, Cokal and Solak gave a complete break to it in [2]. Based on the scheme in [1], we propose a modified scheme which can resist both attacks by simply increasing one key and N horizontal-shifts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then pixel values are modified sequentially using pseudorandom key stream elements produced by a certain qualified chaotic map in the diffusion procedure. This architecture forms the basis of numerous chaos-based image crypto-systems proposed subsequently [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Meanwhile, recent cryptanalysis works have demonstrated that some chaos-based image cryptosystems are insecure against various attacks, and have been successfully broken [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…That means identical key stream will be used to encrypt different plain images if the secret key remains unchanged. This property allows the attacker to launch known-plaintext attack [30][31][32][33]35] or chosen-plaintext attack [17,18,19,20,21] so as to retrieve the equivalent key stream elements. Therefore, to further enhance the security, the key stream elements extracted from the same secret key should better be distinct and related to the plain image [22] the present paper proposes a novel chaos-based image encryption scheme with a dynamic state variables selection mechanism (DSVSM).…”
Section: Introductionmentioning
confidence: 99%